Economics of milk production in Tamil Nadu – A comparative study - Umamageswari, M; Dixit, P K; Sivaram, M (Indian Journal of Dairy Science, 2017)
Cost of milk production is an important economic indicator in assessing the farm household efficiency in milk production as well as basis for price fixation. The study was under taken to analyze the cost and returns of milk production in Coimbatore and Tiruppur districts of Tamil Nadu. The study collected data from 90 milk producers covered by cooperative network and 90 milk producers covered by private dairy. The respondents were classified further into 5 groups (landless, marginal, small, medium and large farmers) based on the land size. The study found that the milk producers covered by private dairy realized slightly higher profits as compared to farmers of cooperative dairy. Feed cost had the highest share in production cost (65.62 % in crossbred; 68.55 % in both local cow and buffalo). The cost per litre of crossbred milk production was higher in the case of large farmers (Rs.18.28) as compared to marginal farmer (Rs.17.24). Whereas, it ranged between Rs.31.36 (small) to Rs.33.09 (large) in the case of local cow while in the case of buffalo, it stretched between Rs. 24.71 (marginal) to Rs. 28.71 (landless).